2012
DOI: 10.1111/j.2041-1626.2012.00131.x
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical properties of novel biodegradable poly ε‐caprolactone–chitosan scaffolds

Abstract: The monolayer scaffolds were suitable for reconstruction of the orbital floor and mandibular defects under light load-bearing conditions. The 3-D scaffolds could be used in the high load bearing-areas only if the forces were directed at their superior aspects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…For several years now, using several synthetic materials as bone substitutes has become more popular due to their better osteoconductive and osteoinductive properties. Recently, our research team developed the technique of Melt Stretching and Multilayer Deposition (MSMD) for fabricating three-dimensional (3-D) scaffolds for bone substitution [1][2][3]. The MSMD scaffolds are specifically designed to have an appropriate interconnecting pore system for enhancing osteogenesis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For several years now, using several synthetic materials as bone substitutes has become more popular due to their better osteoconductive and osteoinductive properties. Recently, our research team developed the technique of Melt Stretching and Multilayer Deposition (MSMD) for fabricating three-dimensional (3-D) scaffolds for bone substitution [1][2][3]. The MSMD scaffolds are specifically designed to have an appropriate interconnecting pore system for enhancing osteogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…A microgroove pattern, typically found on the surfaces has proved to support attachment of osteoblasts [1]. In addition, the mechanical properties of the scaffolds are suitable for withstanding forces occurring in real circumstances of reconstruction in the oral and maxillofacial region [3]. To make the fabricating process easier and more practical, the steps of MSMD were simplified and renamed "modified MSMD (mMSMD) or Melt Stretching and Compression Molding (MSCM)" [4].…”
Section: Introductionmentioning
confidence: 99%
“…1 Our research team developed the novel technique of melt stretching and multilayer deposition (MSMD) specifically for fabricating 3D scaffolds for bone regeneration. 2,3 The MSMD scaffolds are specifically designed to be an appropriate interconnecting pore system for enhancing osteogenesis. A microgroove pattern, typically found on their surfaces, proved to support attachment of osteoblasts.…”
Section: Introductionmentioning
confidence: 99%
“…An interconnecting pore system of those scaffolds is designed to be appropriate for new bone regeneration. In addition, the mechanical testing indicated that the scaffolds are suitable for withstanding forces occurring in real circumstances of the reconstruction in oral and maxillofacial region [14]. Regarding the economical consideration, the cost of the scaffolds is significantly cheaper than importing scaffolds, therefore, MSMD is the main technique for fabricating biodegradable scaffolds in our future studies.According to our study [13], the PCL-20%CS scaffolds achieved the most superior results for supporting osteoblast proliferation, followed by PCL-10%CS scaffolds and pure PCL scaffolds, respectively.…”
mentioning
confidence: 93%